2009
DOI: 10.1080/08923970902814103
|View full text |Cite
|
Sign up to set email alerts
|

Zoledronic acid, an aminobisphosphonate, modulates differentiation and maturation of human dendritic cells

Abstract: Zoledronic acid (ZOL), an effective nitrogen-containing bisphosphonate against excessive bone loss, has been shown affecting the function of cells of both innate and acquired immunity. In this study, we tested the effect of ZOL on differentiation and maturation of human myeloid dendritic cells (DC). When ZOL (1.1 to 10 microM) was added to the culture of starting monocytes, but not to immature DC, the recovery rate of DC was markedly reduced in a concentration-dependent manner. The mature DC differentiated in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 35 publications
2
18
0
Order By: Relevance
“…As we found that ZA inhibits myeloid differentiation in vitro , it can be assumed that the significant increase in the MO-MDSC population found in ZA-treated mice compared with untreated mice are caused by similar inhibitory effects on myeloid differentiation. Inhibition of myeloid differentiation by ZA has also been reported by others (Wolf et al , 2006; Melani et al , 2007; Chen et al , 2009). …”
Section: Discussionsupporting
confidence: 75%
“…As we found that ZA inhibits myeloid differentiation in vitro , it can be assumed that the significant increase in the MO-MDSC population found in ZA-treated mice compared with untreated mice are caused by similar inhibitory effects on myeloid differentiation. Inhibition of myeloid differentiation by ZA has also been reported by others (Wolf et al , 2006; Melani et al , 2007; Chen et al , 2009). …”
Section: Discussionsupporting
confidence: 75%
“…The findings from the present study showed that ZA treatment can suppress Treg levels in peripheral blood while increasing the levels of gdT cells and IL-17 in peripheral blood. BPs can increase the level of IL-17 and gdT cells and decrease the level of Tregs, suggesting that BPs can affect the function of cells in both the innate and acquired immunity pathways [15]. Macrophages could phagocytose apoptotic cells and secrete TGF-b, which could induce Treg differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…When macrophages were sensitized with bisphosphonates, chemokine production was suppressed (40). Bisphosphonates are also able to modulate the maturation of dendritic cells (41). These findings support an immunomodulatory effect of bisphosphonates.…”
Section: Preclinicalmentioning
confidence: 99%